Penyuluhan Budaya Siaga Bencana Siswa SDN 3 Kabila Bone - Ayub Pratama Aris; Ninasafitri Ninasafitri; Masruroh Masruroh; Moch Rio Pambudi; Najmah Najmah; Erga Kurniawati (Universitas Negeri Makassar, 2022)
Disasters in Indonesia can be detrimental every time they occur, Gorontalo, which is on the Pacific plate route, has the potential for disasters to occur, therefore it is necessary to be prepared for disasters, most victims of school-age children, the importance of disaster knowledge from an early age in order to reduce threats to children. among others (before, during, and after a disaster) conducted using the lecture method which is expected to provide an overview of disaster preparedness. from this counseling explains the culture of disaster preparedness where this explanation is carried out for six disasters that often occur in Indonesia. To reduce disaster risk, a culture of preparedness must be instilled from an early age on a regular basis so that disaster preparedness is a step to deal with disasters. disaster preparedness can be improved from a low level of knowledge to be better by implementing a daily disaster preparedness culture